Stress-induced organismal death is genetically regulated by the mTOR–Zeste–Phae1 axis - Takashi Matsumura; Masasuke Ryuda; Hitoshi Matsumoto; Takumi Kamiyama; Kyoko Jinnai; Shu Kondo; Akira Nakamura; Yoichi Hayakawa; Ryusuke Niwa (Proceedings of the National Academy of Sciences, 2025)
All organisms are exposed to various stressors, which can sometimes lead to organismal death, depending on their intensity. While stress-induced organismal death has been observed in many species, the underlying mechanisms remain unclear. In this study, we investigated the molecular mechanisms of stress-induced organismal death in the fruit fly Drosophila melanogaster . We identified a chymotrypsin-like serine protease Phaedra1 ( Phae1 ) as a death mediator in D. melanogaster larvae. Phae1 expression was up-regulated by lethal heat stress (40 °C) but not nonlethal heat stress (38 °C or lower). The most prominent induction of Phae1 occurred in the central nervous system (CNS). We found neuro-specific knockdown of Phae1 increased survival and reduced neuronal caspase activity following exposure to lethal heat stress, suggesting that the transcriptional upregulation of Phae1 in the CNS is essential for stress-induced organismal death. We next found via bioinformatic and biochemical analyses that the transcription factor Zeste (Z) bound the Phae1 enhancer region and that z loss-of-function impaired Phae1 induction in the CNS, increasing survival following lethal heat stress. In addition, we found via chemical screening that rapamycin, a chemical inhibitor of mechanistic target of rapamycin (mTOR), suppressed Phae1 expression. Neuro-specific knockdown of mTor reduced the protein levels of both Phae1 and Z, leading to an increase in survival following lethal heat stress. Together, these results indicate that heat stress–induced organismal death in D. melanogaster larvae is regulated by a genetically encoded transcriptional signaling pathway involving the mTOR–Z–Phae1 axis.